Epidemiology and control of Pseudocercospora angolensis fruit and leaf spot disease on citrus in Zimbabwe - Pretorius, Mathys Cornelius (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2005.